Climate Risk Country Profile : Maldives - World Bank Group (World Bank, Washington, DC and Asian Development Bank, Manila, 2021)
Maldives is an archipelago of 26 low-lying coral atolls in the Indian Ocean, southwest of the Indian subcontinent. Due to its location over the equator in the Indian Ocean, Maldives experiences a typical equatorial monsoonal climate. Maldives experiences warm and humid climate throughout the year, with seasonal fluctuations in temperature and rainfall due to the monsoon. This document aims to succinctly summarize the climate risks faced by Maldives. This includes rapid onset and long-term changes in key climate parameters, as well as impacts of these changes on communities, livelihoods, and economies, many of which are already underway. This is a high-level synthesis of existing research and analyses, focusing on the geographic domain of Maldives, therefore potentially excluding some international influences and localized impacts. The core data presented is sourced from the database sitting behind the World Bank Group’s (WBG) climate change knowledge portal (CCKP), incorporating climate projections from the Coupled Model Inter-comparison Project Phase 5 (CMIP5). This document is primarily meant for WBG and Asian Development Bank (ADB) staff to inform their climate actions. The document also aims and to direct the reader to many useful sources of secondary data and research.